TINJAUAN GEOGRAFI DALAM PERILAKU ADAPTASI MASYARAKAT TERHADAP BENCANA BANJIR DI DESA MOTAAIN KECAMATAN MALAKA BARAT KABUPATEN MALAKA - Sunimbar Sunimbar; Ignasius Suban Angin (Universitas Negeri Gorontalo, 2022)
The research objectives were to: (1) analyze the spatial distribution of the level of flood vulnerability in Motaain Village; (2) know the community's attitude towards the flood disaster in Motaain Village; and (3) know the community's adaptation strategy in dealing with flood disaster in Motaain Village.The type of research is descriptive research, which the type of research that has a purpose to explain specifically a symptom and event that is happening at the present time or an actual problem by using data in the form of quantitative and qualitative data. The study population was 196 heads of families. The sampling technique used is a random sample or random sampling or probability sampling, with a simple random sampling technique. The sample size in this study was 45 families, determined by lottery. Data sources consist of primary data and secondary data. Data collection techniques are: interviews, observation, and documentation. The data analysis technique used is qualitative and quantitative analysis.The results of the study: (1) baed on six parameters, namely soil type, elevation/place, slope, land use, rainfall and river density, the Motaain Village area has two flood-prone zones, namely a moderately vulnerable zone and a very flood-prone zone; (2) the attitude of the community before the flood disaster, during the flood disaster, and after the flood disaster varied; (3) adaptation strategies before the flood disaster, during the flood disaster, and after the flood disaster, the safety of human casualties, the economic aspect, the social aspect, the structural aspect, and the cultural aspect.